Engaging the Canadian Diaspora: Youth social identities in a Canadian border city - Dlamini, S.; Wolfe, Barat; Anucha, Uzo; Yan, Miu (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis paper is based on qualitative interviews undertaken with immigrant youth of African descent in Windsor, Ontario; it describes their sojourner lives across geographic borders and their final settlement in Windsor. The paper also offers narrations of the activities that enabled them to formulate friendships and the barriers and facilitators to the development of friendships across races. Critical findings reported in this paper reveal the ways that youth use resources in their travels to construct and negotiate their identities and to formulate new friendships. An important resource used by the majority of the youth was that of an imagined homeland, which consequently impacted on how they viewed and acted on the racial boundary critical in the formation of friendships in the Diaspora.